2016
DOI: 10.1159/000448278
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Use of Gene Expression Profiles in Estrogen Receptor-Positive Early-Stage Breast Cancer Patients: A Nationwide Study

Abstract: Background: Breast cancer guidelines suggest the use of gene expression profiles (GEPs) in estrogen receptor-positive (ER+) breast cancer patients in whom controversy exists regarding adjuvant chemotherapy benefit based on traditional prognostic factors alone. We evaluated the current use of GEPs in these patients in the Netherlands. Patients and Methods: Primary breast cancer patients treated between January 1, 2011 and December 31, 2014 and eligible for GEP use according to the Dutch national breast cancer g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…An unexpected observation in a previous population-based study was the frequent use of GEPs outside the guideline-intended indicated area, i.e. in patients in whom clinical guidelines state a clear recommendation to administer or withhold CT based on clinicopathological factors alone [12]. GEP use in this patient group raises the question whether the GEP test results influenced CT administration in these patients.…”
Section: Introductionmentioning
confidence: 87%
“…An unexpected observation in a previous population-based study was the frequent use of GEPs outside the guideline-intended indicated area, i.e. in patients in whom clinical guidelines state a clear recommendation to administer or withhold CT based on clinicopathological factors alone [12]. GEP use in this patient group raises the question whether the GEP test results influenced CT administration in these patients.…”
Section: Introductionmentioning
confidence: 87%
“…Patients with grade III tumors were not included, because these patients were not considered candidates for GEP use. Although the 70-GS and OncotypeDx are both commercially available in the Netherlands, OncotypeDx was rarely used during the study period 16. We therefore focused on the use and impact of 70-GS only.…”
Section: Methodsmentioning
confidence: 99%
“…The test was deployed in a limited number of patients, comprising < 10% of the GEPs that were used during the study period [12]. Approximately half of the tests were used outside the intended indication area.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous population-based study, we observed an increase in 70-GS use in Dutch breast cancer patients within the aforementioned guideline-directed indicated area in recent years [12]. When the 70-GS was used in accordance with the Dutch guideline, high adherence rates to the 70-GS test result were observed [13].…”
Section: Introductionmentioning
confidence: 97%